Implementation of Government Communication of the Environmental Service in Waste Management Policy in Dumai Timur District - Siregar, Ira Nur Dewita (Program Pascasarjana UIN Sumatera Utara, 2025)
Waste management is one of the crucial issues in sustainable development in Indonesia. Sustainable development in Indonesia, especially at the sub-districts that have limited resources and infrastructure. This study examines the implementation of government communication by the Environment Office in the waste management policy in Dumai Timur Sub-district, Dumai City. Dumai Timur, Dumai City. Through a qualitative approach with case study analysis, this research highlights how government communication strategies play a role in the effectiveness of waste management policy implementation. The results show that effective communication between the government, community, and other stakeholders determines the success of waste management. However, there are various challenges such as limited facilities, low community participation, and coordination barriers between institutions. Strategic recommendations were developed to strengthen government communication, improve resource capacity, and encourage active community participation in waste management. This study makes an important contribution to the development of more responsive and participatory environmental policies at the local level.